Optimising the Bariatric Patients’ Outcome through Cardiac Rehabilitation Approach - Hanapi, Nor Hanim Mohamad; Yuliawiratman, Brenda Saria; Lai, Lee Lee; Halil, Hazwani; Koo, J.G.; Suhaimi, Anwar (Springer Verlag, 2018)
Bariatric surgery offers a therapeutic alternative with favourable weight management, cardiovascular, metabolic and functional outcomes. Bariatric individuals often have functional impairments pre-operatively that can be addressed to improve postoperative results and eventual functional independence. Multidisciplinary team offers the best approach to address perioperative needs and sustainable weight loss thereafter. We exemplified the application of cardiac rehabilitation therapeutic model in managing two bariatric clients with specific bariatric-related challenges. Our approach focuses on adaptive physical activity, sustainable lifestyle changes to promote post-operative weight loss through education and problem solving as well as secondary prevention of cardiovascular disease. Putting emphasis on addressing physical and psychosocial barriers towards physical activity alongside nutritional aspects potentially confers sustained if not better outcomes on weight reduction and functional improvement.